Al-Attas’s Critique of the Christian-Western Worldview: A Historical-Philosophical Review - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Al-Jadwa: Jurnal Studi Islam, 2025)
The article reflects on the Attasian perspective and epistemology of the West, by highlighting the critique of Syed Muhammad Naquib al-Attas of Western secularism and the production of its modern secular outlook that projected Hellenistic influence on its intellectual and historical tradition, arising from its physical and materialistic concern which contradict with Islamic teaching of ethics and morality and its metaphysical worldview. Its objective is to survey its doctrinal impact on Muslim spiritual life which has caused confusion and error in their vision of reality and truth. The study is based on descriptive-qualitative approaches in the form of literature and documentary survey. The data were analyzed using inductive and deductive method by way of analytic, historical, empirical, hermeneutical, and philological technique. The finding reveals that al-Attas’s critique of the West was designed to dismantle its dewesternization and desecularization framework and the corruption of knowledge and its ideological impact on Muslim society. Its discursive ground was argued in his work on Islamic Metaphysics that defined “Islamic psychology, Islamic cosmology and Islamic ontology” articulating its nature and difference from Western philosophy influenced by its European-Christian thought embedded in its religious experience that make up its substance, premises and values. The research contributes to highlight al-Attas’s philosophical argument and his critique of the West and its contemporary relevance in Muslim society.